2018
DOI: 10.14701/ahbps.2018.22.4.367
|View full text |Cite
|
Sign up to set email alerts
|

A large-cohort comparison between single incision laparoscopic cholecystectomy and conventional laparoscopic cholecystectomy from a single center; 2080 cases

Abstract: Backgrounds/AimsThis study was conducted to verify and compare the safety and feasibility of single incision laparoscopic cholecystectomy (SILC) and conventional laparoscopic cholecystectomy (CLC).MethodsA total of 2,080 patients underwent laparoscopic cholecystectomy in a single center, Konyang University Hospital, between 2010 and 2016. We retrospectively compared the demographics, perioperative outcome, and postoperative complication results between the CLC and SILC groups.ResultsAmong the 2,080 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Previous studies have reported post-operative complications such as bile leakage, bile duct injury, surgical site bleeding, urinary and pulmonary infection, wound infection, seroma, hematoma, incisional hernia, and duodenal perforation. 12,[14][15][16] Like the present study, many studies have found no significant difference in complication rate between SILC and conventional laparoscopic cholecystectomy. 3,13,14 Conversely, one study showed that the incidence of postoperative complications in patients who underwent SILC was lower in conventional laparoscopic cholecystectomy.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have reported post-operative complications such as bile leakage, bile duct injury, surgical site bleeding, urinary and pulmonary infection, wound infection, seroma, hematoma, incisional hernia, and duodenal perforation. 12,[14][15][16] Like the present study, many studies have found no significant difference in complication rate between SILC and conventional laparoscopic cholecystectomy. 3,13,14 Conversely, one study showed that the incidence of postoperative complications in patients who underwent SILC was lower in conventional laparoscopic cholecystectomy.…”
Section: Discussionsupporting
confidence: 66%
“…In previous reports, in the late stage, chronic inflammation tended to result in firm adhesion of the gallbladder to the surrounding organs, which led to scarring and contraction of pericystic tissues [20][21][22] and increased gallbladder wall thickness. Furthermore, increased preoperative leukocytosis was a statistically significant risk factor for conversion to open surgery [23,24].…”
Section: Discussionmentioning
confidence: 85%
“…From initially being labeled as a gimmick, laparoscopic cholecystectomy has become the gold standard in the management of benign gallbladder disease [1]. The wide acceptance of laparoscopy is due to the established benefits of less postoperative pain, better cosmesis, and shorter length of hospital stay, which translates to earlier recovery [2]. Subsequent studies also showed that the smaller the wound, the lesser the operative stress [3].…”
Section: Introductionmentioning
confidence: 99%